Pre-mixing of omega-3 fatty acid-containing liposomes enhances the drug release rate and therapeutic efficacy of anticancer drugs loaded in liposomes - Kim, Eun A.; Choi, Hyeon Gyeom; Nguyen, Bao Loc; Oh, Su Jin; Lee, Soo Bin; Bae, Sung Hun; Park, So Yeon; Kim, Jong Oh; Kim, So Hee; Lim, Soo Jeong (Journal of Controlled Release, 2024)
The therapeutic efficacy of anticancer drugs loaded in liposomes composed of rigid phosphatidylcholine (PC) is hindered by the limited release of these drugs at the tumor site, which in turn hampers delivery of the drug to its intracellular target. In an attempt to improve the therapeutic efficacy of liposomal anticancer drugs, we here explored the use of empty liposomes as “trigger” vehicles to induce drug release from drug-loaded liposomes through liposome-liposome interactions. Empty liposomes containing PC in which omega-3 fatty acids comprised both fatty acid strands (Omega-L) showed a triggering effect on drug release from doxorubicin (DOX)-loaded liposomes (Caelyx). The effectiveness of this triggered-release effect was dependent on the Omega-L composition as well as the mixing ratio of Omega-L to Caelyx. Cryo-TEM and differential calorimetry studies revealed that the Omega-L effect was associated with liposome-liposome interactions that led to loosened membrane packing and increased fluidity of Caelyx. In cultured cells, the intracellular/intranuclear DOX uptake and anticancer efficacy of Caelyx was greatly improved by Omega-L pre-mixing. Intravenous injection of rats with Caelyx, premixed with Omega-L, decreased the area under the plasma concentration-time curve from time zero to time infinity and increased clearance without significantly changing the mean residence time or terminal half-life of DOX compared with Caelyx alone. Ex vivo bioimaging showed that DOX fluorescence in tumors, but not in other organs, was significantly increased by Omega-L premixing. In the mouse xenograft model, premixing of Omega-L with Caelyx suppressed tumor growth 2.5-fold compared with Caelyx. Collectively, the data provide preliminary evidence that the Omega-L–triggered drug release that occurs before and after dosing, particularly at tumor site, improved the therapeutic efficacy of Caelyx. The simple approach described here could enhance the therapeutic value of Caelyx and other anticancer drug-loaded liposomes.
Keywords: Anticancer drug; Caelyx; Doxorubicin; Drug release; Drug release, omega-3-fatty acid, pharmacokinetic, anticancer; Omega-3-fatty acids; Phosphatidyl choline; Premixing; Therapeutic efficacy; Tumor site; Animals; Antineoplastic Agents; Disease Models, Animal; Doxorubicin; Drug Liberation; Fatty Acids, Omega-3; Humans; Liposomes; Mice; Neoplasms; Phosphatidylcholines; Polyethylene Glycols; Rats; Caelyx; Doxorubicin; Drug release, omega-3-fatty acid, pharmacokinetics, anticancer; Liposomes